Modulating Composition and Metabolic Activity of the Gut Microbiota in IBD Patients - Matijašić, Mario (Int J Mol Sci, 2016)
The healthy intestine represents a remarkable interface where sterile host tissues come in contact with gut microbiota, in a balanced state of homeostasis. The imbalance of gut homeostasis is associated with the onset of many severe pathological conditions, such as inflammatory bowel disease (IBD), a chronic gastrointestinal disorder increasing in incidence and severely influencing affected individuals. Despite the recent development of next generation sequencing and bioinformatics, the current scientific knowledge of specific triggers and diagnostic markers to improve interventional approaches in IBD is still scarce. In this review we present and discuss currently available and emerging therapeutic options in modulating composition and metabolic activity of gut microbiota in patients affected by IBD. Therapeutic approaches at the microbiota level, such as dietary interventions alone or with probiotics, prebiotics and synbiotics, administration of antibiotics, performing fecal microbiota transplantation (FMT) and the use of nematodes, all represent a promising opportunities towards establishing and maintaining of well-being as well as improving underlying IBD symptoms.